Perceived Effectiveness Of Social Media As An Advertising And Marketing Tool In Faith-Based Higher Education Institution - Itje Rosali Polii; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
In the digital age, social media has emerged as a powerful communication tool for higher education institutions to engage with students and disseminate information. This study aims to examine students’ perceptions of the appeal of Instagram advertisements as an informational medium at a faith-based private university. Employing a descriptive research design, primary data were collected through the distribution of questionnaires to students at a faith-based university located in Airmadidi, North Sulawesi. The study involved a purposive sample of 200 respondents, selected based on their active use of Instagram and their following of the university’s official Instagram account. Data were analyzed using descriptive statistical techniques. The findings indicate that students' perceptions have a significant positive influence on the perceived appeal of Instagram advertisements as an effective medium for university-related information. These results suggest that faith-based universities can strategically leverage social media platforms like Instagram to enhance their communication and engagement with students.